2020
DOI: 10.1002/ehf2.12782
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and risk of new‐onset and recurrent heart failure: a systematic review and meta‐analysis

Abstract: Despite mounting evidence of the positive relationship between diabetes mellitus (DM) and heart failure (HF), the entire context of the magnitude of risk for HF in relation to DM remains insufficiently understood. The principal reason is because new-onset HF (HF occurring in participants without a history of HF) and recurrent HF (HF re-occurring in patients with a history of HF) are not discriminated. This meta-analysis aims to comprehensively and separately assess the risk of new-onset and recurrent HF depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 147 publications
(385 reference statements)
0
19
0
2
Order By: Relevance
“…The risk magnitudes between HFpEF and HFrEF were not significantly different in studies that examined the risk in both syndromes (p = 0.86), whereas for recurrent HF, the pooled RR (95% CI) of 38 studies was 1.39 (1.33-1.45). These data indicate that, in patients with DM, the magnitude of risk for new-onset HF and recurrent HF is large and DM is associated with a high incidence of both HFpEF and HFrEF [9].…”
Section: Introductionmentioning
confidence: 77%
“…The risk magnitudes between HFpEF and HFrEF were not significantly different in studies that examined the risk in both syndromes (p = 0.86), whereas for recurrent HF, the pooled RR (95% CI) of 38 studies was 1.39 (1.33-1.45). These data indicate that, in patients with DM, the magnitude of risk for new-onset HF and recurrent HF is large and DM is associated with a high incidence of both HFpEF and HFrEF [9].…”
Section: Introductionmentioning
confidence: 77%
“…It is possible that high blood pressure plays a less prominent role in the development of ischemic heart disease in women, which would be more related to other cardiovascular risk factors, such as diabetes [ 23 , 26 ]. HF risk is higher in women with diabetes than in men with diabetes [ 23 , 26 , 27 , 28 ]. Analyzing the characteristics of women with ischemic etiology, we have observed that the clinical profile of these patients is more similar to men with ischemic HF than to women with HF of non-ischemic etiology, suggesting that several differences associated with sex might be, in fact, related to ischemic etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Prin urmare, pe lângă reducerea morbidității și mortalității în IC-FES, terapia cu sacubitril/ valsartan ar putea oferi beneficii metabolice suplimentare la pacienții cu diabet zaharat. În plus, aceste date ar putea sugera că pacienții cu diabet zaharat care primesc sacubitril/ valsartan pentru tratamentul IC ar putea necesita ajustarea dozei de terapie hipoglicemiantă (Kodama et al, 2020).…”
Section: Sacubitril/valsartan șI Diabetul Zaharatunclassified